PENGARUH PELATIHAN DAN LINGKUNGAN ORGANISASI TERHADAP KINERJA PENYULUH PERTANIAN PADA DINAS TANAMAN PANGAN DAN HORTIKULTURA KABUPATEN ROKAN HULU - Oktavia, Mega; Anwar, Arfianti Novita; Novianti, Devi (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2026)
This study aims to determine the simultaneous influence of training and organizational environment on the performance of agricultural extension workers at the Food Crops and Horticulture Service of Rokan Hulu Regency. The population of this study was all employees of the Food Crops and Horticulture Service of Rokan Hulu Regency. The sampling technique used saturated sampling with 54 respondents. The independent variables in this study were training (X1), organizational environment (X2), and performance variables (Y). Data collection methods used questionnaires, documentation, and informal interviews. Instrument reliability tests included validity and reliability tests, classical assumption tests included normality tests, multicollinearity tests, and heteroscedasticity tests. Data analysis used multiple linear regression analysis using the SPSS program. The results showed that 97.1% of performance was influenced by training and organizational environment, while the remaining 2.9% was influenced by other variables not examined in this study. The conclusion of this study, based on the results of partial and simultaneous testing, is that training and organizational environment have a significant influence on the performance of agricultural extension workers.